A cross-sectional study to find out the prevalence, pattern, risk factors, comorbidities and severity of vascular depression in patients attending psychiatric outpatient department in a tertiary care centre - Nigam, Sandeep; Shukla, Madhukar Prasad; Bhushan, Samhita (International Journal of Research in Medical Sciences, 2022)
Background: Depression was declared as the second major cause of disability adjusted life years (DALY) in 2020 and the economic burden experienced by those with depression is next to coronary artery disease. Vascular depression has late age at onset 60 years or older, nonpsychotic subtype, with no family history of mental disorders, presenting with loss of pleasure and functional disability. Depression is accompanied by cerebrovascular lesions as determined by MRI and not accompanied by neurological signs. This has a spiral correlation with various comorbidities leading to diagnostic enigma at one hand and worsened prognosis on the other. This emphasized the early diagnosis and treatment to improve the quality of life. Methods: Patients with age more than 60 years, of either sex, with a mini GDS score ≥5, having the first episode of depression and who gave consent were included. Results: Hypertension thus emerged as a significant risk factor and was positively associated with increased severity of depression. Conclusions: Subclinical cognitive impairment and mild cognitive impairment (MCI) may precede years before the onset of vascular depression. Prompt detection and management of these entities and associated risk factors could prevent or postpone impending vascular depression.